NSAIDs in Sports Medicine: Balancing Quick Relief with Long-Term Health Impacts - Wojciech Urbański; Natalia Dolata; Bartosz Balcer; Adrianna Kruczkowska; Emil Bulzacki; Agnieszka Cebula; Maja Weimann; Aleksandra Stosiek; Mateusz Pakuła; Paweł Liszka (Quality in Sport)
Introduction and Purpose Nonsteroidal anti-inflammatory drugs (NSAIDs) are regularly used in sports medicine to manage pain and inflammation caused by acute and chronic injuries. Their mechanism involves inhibition of cyclooxygenase (COX) enzymes, reducing the body’s natural inflammatory response. This review aims to analyze the effects of NSAID use in sports contexts, focusing on short- and long-term benefits and risks, specifically concerning tissue healing, athletic performance, and general health outcomes. Materials and Methods We reviewed studies from PubMed, Google Scholar and ResearchGate, focusing on key search terms including NSAIDs in sports injuries, NSAID mechanism, short-term and long-term effects of NSAIDs, athletic performance and NSAID, pain management in sports, NSAID side-effects and NSAID alternatives Conclusions Short-term NSAID use can provide effective pain relief and support functional recovery, benefiting professional and recreational athletes in their sports. However, prolonged use may decrease natural tissue healing abilities, increase susceptibility to various side effects, and potentially affect long-term performance. Alternative pain management strategies are recommended to complement NSAID use, providing athletes with safer, long-term options for recovery. This review highlights the need for a balanced approach to NSAID usage, recommending cautious decision making among sportspeople, coaches, and healthcare workers.